The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1111/j.1399-3054.1979.tb02635.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production by Tobacco (Nicotiana tabacum) Callus

Abstract: Tobacco callus cultures grown on defined agar-solidified media produced ethylene in differing amounts, which were related to cultural treatment and age of the callus. There was a close correlation between the rate of etbylene production and growth. In darkness, maximal rates occurred in the third week of growth with ethylene production in the range of 750 ni (calius piece)^^ d^' (fr, wt, = 1,5 g),, and in the light, maximal rates occurred in the first week of growth, 200 nl (callus piece)"' d"' (fr, wt, = 200 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

1983
1983
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Whether AtEBP expression in callus is due to elevated ethylene levels or other factors is not clear. There are conflicting reports on ethylene production in callus cultures and the amount of ethylene produced appears to be dependent on the culturing conditions (41). Chitinases have been shown to be inducible by ethylene in yam callus (42), suggesting that ethylene levels are not saturating in this tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…Whether AtEBP expression in callus is due to elevated ethylene levels or other factors is not clear. There are conflicting reports on ethylene production in callus cultures and the amount of ethylene produced appears to be dependent on the culturing conditions (41). Chitinases have been shown to be inducible by ethylene in yam callus (42), suggesting that ethylene levels are not saturating in this tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on lavandin callus cultures showed that callus growth was not affected by ethylene production (Mensuali-Sodi et al, 1989), but the regeneration of lavandin callus was associated with a low rate of ethylene production (Panizza et al, 1997). Conversely, a close positive correlation between ethylene production and callus growth was found in tobacco (Huxter et al, 1979) as well as in carob callus cultures (Martins-Loucao and Rodriguez-Barrueco, 1983) . From these results, a clear conclusion has not been drawn on the interaction between ethylene production and the growth in tissue culture.…”
Section: Discussionmentioning
confidence: 95%
“…In plant tissue and cell cultures, the cells are fairly uniform and undiffe~entiated and it is possible to study the studies also gave different results about the correlation between ethylene production and growth even in the same species (Huxter et al, 1979;Koves and Szab6, 1987). It is also known that dicot plants produce a larger amount of ethylene and are more sensitive to· exogenous ethylene than monocot plants (Tittle et al, 1990;Grossmann and Kwiatkowski, 1993).…”
mentioning
confidence: 99%
“…The influence on ethylene, 1-aminocyclopropanecarboxylic acid (ACC), and N-malonyl-ACC (MACC) Undifferentiated plant cell suspensions are able to produce ethylene depending on the kind of plant from which the cell originated but also on their physiological state (2-4, 15, 17, 21, 24). With respect to its physiological significance, data suggested no functional relationship between growth and ethylene synthesis (10,15,24). Ethylene was assumed to be a by-product of actively dividing cells.…”
mentioning
confidence: 99%
“…With respect to its physiological significance, data suggested no functional relationship between growth and ethylene synthesis (10,15,24). Ethylene was assumed to be a by-product of actively dividing cells.…”
mentioning
confidence: 99%